PENGARUH PEMBERIAN ATORVASTATIN TERHADAP PERUBAHAN PROFIL LIPID DAN PETANDA INFLAMASI IL-6 PADA PASIEN DIABETES DENGAN DISLIPIDEMIA - Rezlie Bellatasie, 051515153003 (2017)
Background Diabetes is associated with an increase of macrovascular complications such as cardiovascular disease and stroke 2-4 times higher than individuals without diabetes and it is the highest cause of mortality in DM patients. Dyslipidemia is one of comorbid in diabetic disease characterized by increased small dense LDL, elevated triglycerides and decreased HDL. IL-6 is one of pro inflammatory cytokine that can be used to assess inflammatory conditions in DM and its complications. Atorvastatin is one of the statin drugs effective to lower LDL values. Atorvastatin also has a pleiotropic effects to reduce inflammatory markers. Objectives The aim of this study is to analyze the effect of atorvastatin 20 mg administration on lipid profile and inflammatory marker IL-6 after 30 days of therapy and correlation between lipid profile and IL-6. Material and Method An observational prospective cohort study conducted from November 2017 to January 2018 approved by ethical committee of General Hajj Hospital, Surabaya. Nineteen patients who meet the inclusion criteria and signed the informed consent were enrolled in this study. The measurement of lipid profile and IL-6 level were done twice, before and after 30 days of therapy. Results After atorvastatin administration, there was a 40.55% decrease in LDL level (pre=163.47±28.77; post= 97.89±29.71), a 15.34% decrease in TG level (pre=161.89±76.12; post= 132.21±75.48), a 30.70% decrease in total cholesterol level (pre=232.84±43.19; post 161.89±44.73) which statistically significant (p<0.05). There was a 6.06 % increase in HDL level but not statistically significant (p>0.05). The IL-6 level was decrease by 5.75% (pre=4,304 ± 3,445; post=4,061 ± 3,763) but not statistically significant (p>0.05). Conclusion From this study, it can be concluded that atorvastatin administration can improve lipid profile in diabetes patients with dyslipidemia. There was a decrease of IL-6 but not statistically different.